(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is a complex condition that affects social communication and behavior, resulting from a combination of genetic, environmental, immunological, neurological, and gastrointestinal factors. In recent years, research has focused on better understanding these risk factors and their relationship to the development of ASD. The link between gut microbiota and autism has been widely studied, highlighting the importance of diet in the health of individuals with autism. Eating problems are common in this population, reinforcing the need for adequate nutritional support from an early age to promote a better quality of life. This study aims to investigate how gut microbiota interferes in children with Autism Spectrum Disorder (ASD) and its possible nutritional interventions aimed at reducing the symptoms present in ASD through a literature review. The present study was based on a literature review on the topic and utilized the following databases: Google Scholar, PUBMED, and BIREME. National and international scientific articles in Portuguese and English published between 2013 and 2024 were analyzed. The results of this literature review highlight the significant influence of gut microbiota on symptom management in children with autism, where dysregulation of the microbiome and chronic inflammation worsen autistic symptoms. A multidisciplinary approach that includes nutritional intervention and family support is essential to improve the quality of life for autistic children, promoting their overall development and autonomy.